Guidelines for Operating Businesses for Elderly in Thailand - Boonrattanakul, Wongtawat; Siljaru, Tanin; Worawattanaparinya, Sakrapee (Princess of Naradhiwas University Journal, 2021)
According to the continuous increase number of elderly population, Thailand is stepping into aged society, resulting in business sector to adjust itself to meet the changes of the target customers, most of whom are the elderly. This research aimed 1) to study the operational characteristics of businesses for elderly in Thailand, 2) to study the latent variables of the guidelines for operating businesses for elderly in Thailand and 3) to develop the structural equation model of the guidelines for operating businesses for elderly in Thailand. For the qualitative part, the in-depth interview technique was used to collect data from 9 experts, and the focus group was applied to gather information from 7 advisors. For the quantitative part, questionnaires were used to collect data from 500 entrepreneurs engaged in businesses related to the elderly which the samples were selected by multi-stage sampling. The descriptive, inference, and multivariate statistics were used to analyze the data. The study revealed that the characteristics for operating businesses for the elderly in Thailand, were the top 3 highest percentage score which were 1) organizations still have not been members of any associations of the elderly of Thailand at 95.8 percent 2) medical and health products were needed by the late elderly (80 years and over) at 51.8 percent 3) organizations created innovations for elderly cooperating with private organization at 50.6 percent. The highest mean score in the aspects of the guidelines for operating businesses for the elderly in Thailand were as follows: Innovation & Technology; purchasing some parts of or whole technology from outside to be further applied, Internal process; improving organizations to be more flexible in order to be ready for supporting changes, Marketing; products should be easy to use and services should be easy to access, convenient, and not complicated, Resources; supporting the elderly to co-invest in businesses and Learning & Development; career path should clearly be specified. The analysis of the developed structural equation model showed that it passed the assessment criteria and was consistent with the empirical data. Its values of Chi-square Probability Level (CMIN-p), Relative Chi-square (CMIN/DF), Goodness of Fit Index (GFI), and Root Mean Square Error of Approximation (RMSEA) were 0.087, 1.109, 0.951 and 0.015, respectively.